Ionic liquids in biotransformations and organocatalysis solvents and beyond - Domínguez de María, Pablo, 1974- (Hoboken, N.J. : Wiley, 2012)
"This book addresses the use of ionic liquids in biotransformation and organocatalysis. Its major parts include: an overview of the fundamentals of ionic liquids and their interactions with proteins and enzymes; the use of ILs in biotransformations; non-solvent applications such as additives, membranes, substrate anchoring, and the use of ILs in organocatalysis (from solvents to co-catalysts and new reactivities, as well as non-solvent applications such as anchoring and immobilization)"--Provided by publisher.
pt. I. Fundamentals -- pt. II. Ionic liquids in biotransformations -- pt. III. Ionic liquids in organocatalysis.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Proteins -- Biotechnology; Ionic solutions; Catalysis; Electronic books